Hubungan Sistem Rekrutmen, Seleksi dan Pelatihan terhadap Kinerja Perawat di RS Aisyiyah Kota Pariaman - Viani, Syafina Annisa; Sari, Marta Widian; Sari, Silvia (Lembaga Yasin AlSys, 2025)
The recruitment process is not appropriate in selecting prospective nurses in accordance with the needs of the hospital, selection is not rigorous or objective to the competence of prospective nurses, and training is inadequate or irrelevant to the advancement of nursing science. The purpose of this research is to study how the training, recruitment, and selection system at Aisyiyah Hospital in Pariaman City affects the performance of nurses which in turn will have an impact on the quality of service to patients. The research method used is quantitative research. The analysis method used is validity test, reliability test, descriptive analysis test, path coefficient, regression test and hypothesis testing using SmartPLS 4 software to identify the relationship between the research variables The sample taken by the researcher includes a population of all nurses at Aisyiyah Hospital in Pariaman City, which is 67 people. Therefore, researchers used saturated sampling with data collection techniques through distributing questionnaires. The results showed that the recruitment and training system had an insignificant effect on nurse performance, and selection had a significant effect on nurse performance. While the recruitment system, selection and training simultaneously have a significant effect on nurse performance. This conclusion provides important insights for policy makers and companies in understanding the importance of recruitment, selection and training.